2005
DOI: 10.5713/ajas.2005.277
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Antioxidant Effects in Melanins Extracted from Various Tissues of Animals

Abstract: This study was carried out to investigate the antioxidant effects of melanin extracts, including silkie fowl skin melanin (SS-melanin), silkie fowl comb melanin (SC-melanin), sepia ink sac melanin (SE-melanin), octopus ink sac melanin (OC-melanin) and synthetic melanin (SY-melanin). The results showed that with the addition of melanin extracts, linoleic acid peroxide significantly, decreased (p<0.05) with the increase in the irradiative time of UV and that OC-melanin had the highest efficiency on antioxidant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 16 publications
(19 reference statements)
0
15
1
2
Order By: Relevance
“…They showed that squid melanin scavenge hydroxyl free radical remarkably which are indicators of the antioxidant properties of squid melanin. Lin and Chen (2005) also isolated melanin from cuttlefish (Sepia) ink and investigated the antioxidant properties, and they found high antioxidant value. Lei et al (2008) also found antioxidant effects of melanin-Fe squid ink when they were using it as a treatment for iron deficiency anaemia (IDA) in rats.…”
Section: Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that squid melanin scavenge hydroxyl free radical remarkably which are indicators of the antioxidant properties of squid melanin. Lin and Chen (2005) also isolated melanin from cuttlefish (Sepia) ink and investigated the antioxidant properties, and they found high antioxidant value. Lei et al (2008) also found antioxidant effects of melanin-Fe squid ink when they were using it as a treatment for iron deficiency anaemia (IDA) in rats.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…We declare that we have no conflict of interest. • High melanin concentration showed good antioxidant activity Lin and Chen (2005) Girija, A.S., Suba, K.P., Hariprasad, G. and Raghuraman, R. (2014). A novel study on the antibacterial effect of the crude squid ink extracts from the Indian squid against four bacterial pathogens isolated from carious dentine.…”
Section: Conflict Of Interest Statementmentioning
confidence: 99%
“…The melanin extract from silkie fowl skin had reducing and chelating power against Fe 2+ [9]. A recent study reported the antioxidant activity of melanin from Aspergillus nidulans [21].…”
Section: Discussionmentioning
confidence: 99%
“…Melanin dapat mengikat Fe 2+ dikarenakan terdapat struktur 2-carboxyl indole yang dapat berikatan kuat dengan Fe 2+ . 13 Tinta cumi juga memiliki kandungan DHI dan DHICA yang mempunyai karakter kuat untuk menyerap struktur -OH dan -NH yang membuktikan bahwa kandungan ini memiliki kemampuan antioksidan dengan Inhibitory Concentration (IC50) dalam pembersihan O 2 -(superoksid) lebih efisien dibandingkan dengan obat antioksidan komersil (Carnosin) dan dalam pembersihan -OH kedua zat ini memiliki nilai yang sama. 14 Dengan adanya antioksidan, mekanisme modifikasi oksidatif kolesterol LDL menjadi LDL-oks itu tidak akan terjadi karena antioksidan akan mengikat radikal bebas, sehingga semua akibat lanjut dari modifikasi oksidatif kolesterol LDL dapat dicegah.…”
Section: Hasil Penelitian Dan Bahasan Pengaruh Pemberian Ekstrak Tintunclassified